Human Ezrin-Moesin-Radixin Proteins Modulate Hepatitis C Virus Infection - Bukong, Terence N. (2013)
Host cytoskeletal proteins of the ezrin-moesin-radixin (EMR) family have been shown to modulate single-stranded RNA virus infection through regulating stable microtubule formation. Antibody engagement of CD81, a key receptor for HCV entry, induces ezrin phosphorylation. Here we tested the role of EMR proteins in regulating HCV infection and explored potential therapeutic targets. We show that HCV E2 protein induces rapid ezrin phosphorylation and its cellular redistribution with F-actin via spleen tyrosine kinase (SYK). Therapeutically blocking the functional roles of SYK or F-actin reorganization significantly reduced Huh7.5 cell susceptibility to HCV J6/JFH-1 infection. Using gene regulation, real-time quantitative PCR, western blot and fluorescent microscopy analysis, we found that proteins of the EMR family differentially regulate HCV infection in the J6/JFH-1/Huh7.5 cell system. Moesin and radixin, but not ezrin, expression were significantly decreased in chronic HCV J6/JFH-1 infected Huh7.5 cells and HCV infected patient liver biopsies compared to controls. The decreases in moesin and radixin in HCV J6/JFH-1 infected Huh7.5 cells were associated with a significant increase in stable microtubules. Ezrin knockdown inhibited immediate post-entry events in HCV infection. Over-expression of moesin or radixin significantly reduced HCV protein expression. In contrast, transient knockdown of moesin or radixin augmented HCV infection. Making use of the Con1 HCV replicon system, we tested the effect of EMR proteins on HCV replication. We found that transient knockdown of moesin increased HCV RNA expression while over-expression of EMR showed no significant effect on HCV replication. Our findings demonstrate the important role of EMR proteins during HCV infection at the post-entry level and highlight possible novel targets for HCV treatment.